MBRS-06. THE ROLE OF G-CSF RECEPTOR SURFACE EXPRESSION IN MEDULLOBLASTOMA PATHOGENESIS. Issue 2 (22nd June 2018) - Paul, Megan; Zage, Peter
Abstract: Medulloblastoma recurrence portends a dismal prognosis. Identifying sub-populations of medulloblastoma tumors with stem cell-like properties holds promise for reducing disease recurrence, but no unifying marker of medulloblastoma cancer stem cells has been found. The granulocyte stimulating factor receptor (GCSF-R) is well understood in the context of hematopoiesis. Neuroblastoma and melanoma cells subpopulations that express the GCSF-R have cancer stem cell properties of chemoresistance and increased tumorigenicity and are enriched in tumors after after chemotherapy administration. GCSF-R activation after ligand binding leads to signaling through the JAK-STAT pathway, suggesting a potential therapeutic target. Using flow cytometry, we show that a subpopulation of medulloblastoma cells in a panel of cell lines express GCSF-R, and that the GCSF-R-positive subpopulations have a slower growth rate than GCSF-R-negative or mixed populations. Subpopulations of medulloblastoma cells that express the GCSF-R are also more chemoresistant in vitro to vincristine, etoposide, and carboplatin. We also show that Ruxolitinib, a JAK1/2 inhibitor used in the treatment of polycythemia vera, has in vitro activity against medulloblastoma cell lines, suggesting that JAK/STAT inhibition is an effective therapy against medulloblastoma. With the common use of G-CSF to promote bone marrow recovery in children with medulloblastoma and the potential role of the GCSF-R as a cancer stem cell marker, we propose that JAK inhibition may represent an adjunct therapy targeting overall tumor burden and specifically targeting slow-growing, GCSF-R-positive, cells that may drive recurrence.